2015
DOI: 10.3109/23744235.2015.1109134
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and its clinical relevance in oesophageal squamous cell carcinoma in a Kurdish population in the west of Iran

Abstract: Background The aetiological role of Human Papillomavirus (HPV) in oesophageal squamous cell carcinoma (ESCC) was evaluated by assessment of the presence and status of HPV DNA in a Kurdish population in the west of Iran. Methods One hundred and three paraffin-embedded ESCC tissue samples, diagnosed between 2007-2013, were included in the study. DNA was extracted and then HPV presence and genotypes were determined by PCR and INNO-LiPA genotyping, respectively. Results HPV DNA was detected in 11/103 (10.7%) of ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Global data shown by recent literature indicates that HPV has no significant etiological role in most cases of ESCC 35 . Another recent study showed that HPV infection may play a role in esophageal carcinogenesis only in high-incidence regions 41 and this conclusion corroborates, in part, the results demonstrated by our study, since we found identical HPV frequency in patients without EC group compared to the group with ESCC. To confirm, no correlation with p16 and p53 expression with tumor was observed and they are canonic pathways altered in HPV-cervical cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Global data shown by recent literature indicates that HPV has no significant etiological role in most cases of ESCC 35 . Another recent study showed that HPV infection may play a role in esophageal carcinogenesis only in high-incidence regions 41 and this conclusion corroborates, in part, the results demonstrated by our study, since we found identical HPV frequency in patients without EC group compared to the group with ESCC. To confirm, no correlation with p16 and p53 expression with tumor was observed and they are canonic pathways altered in HPV-cervical cancer.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous study, the association of HPV-16 and HPV-18 with ESCC was shown in Kurdish population of the west of Iran (4), 4 where the incidence of the disease is low (7 and 8.1 in 100 000 in Kurdistan 20 and Kermanshah provinces, 21 respectively) in comparison with an incidence of 1/1000 in some populations of Iran such as high-risk Turkmen population in the north of Iran. 22 Using real-time PCR, we examined the presence of HPV-18 and HPV-16 and also the integration status of the virus, since HPV integration is considered to result in the deletion of E2 gene.…”
Section: Discussionmentioning
confidence: 96%
“…2 Recent studies have reported HPV DNA detection in extragenital cancers as well; even though the etiological association of HPV in those malignancies is still contentious. [3][4][5] One of the main procedures of HPV which induce carcinogenesis is the integration of its genome into the host DNA. 6,7 However, the physical status (episomal/integral) of HPV genome is not absolute for the carcinogenesis and confirmation of insertional mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of HPV integrates into the host cell chromosome in malignant tissues and disrupts E2 ORF. Therefore, decreased expression of E2 regulatory protein results in an increased expression of the viral E6 and E7 oncoproteins (9).…”
Section: Introductionmentioning
confidence: 99%